Eletroconvulsoterapia e o impacto na taxa de internações psiquiátricas - Coppini Júnior, Luiz Antonio (2022)
Electroconvulsive therapy is the most consolidated, studied, and safe semi-invasive neuromod- ulation procedure in psychiatry. The safety of the procedure with technological advances pro- vides comfort for the patient with minimal side effects. It is indicated for depression, mania, schizophrenia, catatonia, neuroleptic malignant syndrome, status epilepticus and Parkinson's disease. The objective of this study was to determine the impact of electroconvulsive therapy on the psychiatric admission rate at the University Hospital of Santa Maria, in addition to epi- demiologically characterizing this sample and determining the safety of the procedure. For this, a mirror-image study was carried out with psychiatric patients who underwent electroconvul- sive therapy from January 2018 to December 2018 (16 patients) comparing the psychiatric hos- pitalizations of these patients 2 years before and 2 years after the procedure. An epidemiological characterization of patients undergoing electroconvulsive therapy from January 2018 to De- cember 2020 was also carried out, accounting for a total of 48 patients. There was a predomi- nance of men (62.5%), diagnoses of schizophrenia (33%) and bipolar disorder (33%). There was a balanced distribution between the positions of the electrodes between bitemporal (52%) and bifrontal (48%). Regarding the wavelength, the highest frequency was 1.0 (60%) compared to 0.5 (40%). It was also noted that patients with the bifrontal position of the electrodes had a higher frequency of wavelength of 0.5, while patients with a bitemporal position had a higher frequency of wavelength 1.0 (p<0.001). A significant difference was found between the groups, with the highest load values presented by the group with bitemporal electrode placement (pvalue 0.020) and with wavelength 1.0 (p-value 0.025). There was a reduction of 68.64% in the mean number of psychiatric hospitalizations at University Hospital of Santa Maria in the profile of patients analyzed after undergoing electroconvulsive therapy (p-value 0.021). The present study observed a significant reduction in the mean number of psychiatric hospitalizations after patients had been submitted to a cycle of electroconvulsive therapy or had continued to perform it during the period of data analysis. Thus, the study reflected what is already observed in other services and confirmed the quality work that has been performed at the University Hospital of Santa Maria.